Digital marketing and social networks as an innovation opportunity for micro and small companies: a study carried out with retailers in the city of Lavras – MG - de Andrade Ferreira, Cassiano de Andrade Ferreira; Cristina Campos, Rafaella; Mariano Naves, Fernanda; Barati da Silva, Wanessa; Guimarães Fernandes, Gislaine (Seven Editora, 2023)
When the environment becomes increasingly competitive, companies seek different forms of marketing to win and retain customers in an attempt to expand their sales. Therefore, the present work had as its main objective to evaluate the effectiveness of social networks as a marketing strategy for capturing, customer loyalty and expanding sales of micro and small companies (MSEs) in the city of Lavras-MG. Quantitative, descriptive-exploratory research was carried out, through the application of structured questionnaires applied to a sample of 92 MPEs located in the municipality. The results showed that the MSEs analyzed the use of digital social networks as a marketing tool, which has contributed to increased customer acquisition, and customer loyalty and, consequently, to increase sales rate. DOI: https://doi.org/10.56238/devopinterscie-129